ACADEMIC STRESS OF FINAL-YEAR STUDENTS OF THE NURSING STUDY PROGRAM: A CROSS-SECTIONAL STUDY WITH THEIR SLEEP QUALITY - Dewi, Aliana; Wiratmo, Puji Astuti; Mussyarifah, Ratu Fiddini; Pamungkas, Indra Gilang (Fakultas Keperawatan, Universitas Klabat, 2024)
Background: Academic stress is a condition when students react in the form of negative behavior or emotions that arise because of academic demands, or anything related to teaching and learning activities. The types of academic stress felt by students are lack of rest time, busy assignments, competition with friends, fear of change, and failure to obtain results from the academic demands that have been carried out. Purposes: This study aims to assess the relationship between academic stress and sleep quality in final-year students of the nursing study program. Methods: This research used a cross-sectional research design with a total of 93 respondents. Sampling used a total sampling technique. Data were collected using the instruments The Perception of Academic Stress Scale and the Pittsburgh Sleep Quality Index (PSQI) and analyzed using the chi-square test. Results: This research shows that there is a significant relationship between academic stress and sleep quality in final-year students of the nursing study program with a p-value of 0.01 (p-value < 0.05). Individuals who feel stressed will cause hormones such as epinephrine, norepinephrine, and cortisol to affect the central nervous system, causing a state of wakefulness and increasing the alertness of the central nervous system. Conclusion: There is a significant relationship between academic stress and sleep quality. An academic stress management approach through an intervention program can have a positive impact on the sleep quality of nursing students. Latar Belakang: Stres akademik merupakan suatu kondisi ketika mahasiswa bereaksi dalam bentuk perilaku atau emosi negatif yang timbul karena tuntutan akademik, atau segala sesuatu yang berhubungan dengan kegiatan belajar mengajar. Jenis stres akademik yang dirasakan oleh mahasiswa adalah kurangnya waktu istirahat, padatnya tugas, persaingan dengan teman, takut akan perubahan, dan tidak memperoleh hasil dari tuntutan akademik yang telah dilaksanakan. Tujuan: Penelitian ini bertujuan untuk mengkaji hubungan antara stres akademik dengan kualitas tidur pada mahasiswa tingkat akhir program studi keperawatan. Metode: Penelitian ini menggunakan desain penelitian cross-sectional dengan jumlah responden sebanyak 93 orang. Pengambilan sampel menggunakan teknik total sampling. Data dikumpulkan dengan menggunakan instrumen The Perception of Academic Stress Scale dan Pittsburgh Sleep Quality Index (PSQI) serta dianalisis menggunakan uji chi-square. Hasil: Penelitian ini menunjukkan bahwa terdapat hubungan yang signifikan antara stres akademik dengan kualitas tidur pada mahasiswa tingkat akhir program studi keperawatan dengan p-value sebesar 0,01 (p-value < 0,05). Individu yang merasa stres akan menyebabkan hormon seperti epinefrin, norepinefrin, dan kortisol memengaruhi sistem saraf pusat, sehingga menyebabkan keadaan terjaga dan meningkatkan kewaspadaan sistem saraf pusat. Kesimpulan: Terdapat hubungan yang signifikan antara stres akademik dan kualitas tidur. Pendekatan manajemen stres akademik melalui program intervensi dapat memberikan dampak positif terhadap kualitas tidur mahasiswa keperawatan